ANALISIS STRATEGI PEMASARAN DALAM PENGEMBANGAN USAHA SUKASIHSHOP - Sukasih, Emiliana; Rini Hapsari, Veneranda; S.E.,M.M, Usman, (Politeknik Negeri Jakarta, 2024)
The purpose of this research is to understand the analysis of product placement strategies in the growth of Sukasihshop in relation to customer loyalty. This research was conducted at the SukasihShop business located in West Bengkayang. This research uses a qualitative research design with library research methodology. Data collection techniques are carried out through observation, questionnaires and comments. E-Commerce is a platform where meetings between sellers and buyers can occur indirectly (Andriyanty & Lestari, 2022). Where e-commerce plays an important role in the sales and purchasing process, where this activity involves many parties. It can also be understood from a sales concept that e-commerce is included in e-business. Where e-commerce is the best initiative for a business, and with better e-commerce, it is believed that a business will be successful because it has fulfilled the market's desires. It is also known that e-commerce can connect many people from various places through the same media. With better e-commerce, it is believed that a business will be successful because it has fulfilled the market's desires. It is also known that e-commerce can connect many people from various places through the same media. Keywords: technical analysis, foreign flow, false signal